Screening of Acetic Acid-Producing Bacteria from Coffee Pulping Process and Their Efficiency in Malt Vinegar Production - Gizatie Dereje; Chandran Masi; Mesfin Tafesse (Journal of Chemistry)
Bacterial isolate which can produce acetic acid has been isolated from a coffee pulping process. Primary screening of acetic acid-producing bacteria was performed by using YPG medium. Then, positive isolates on YPG were further screened on GYC medium. It has been identified by using a molecular method by sequencing 16srRNA gene and was very closely related to Pseudomonas aeruginosa. Its optimum growth conditions have been optimized by design expert software by using the RSM method. Temperature, ethanol content, pH, and time of incubation of the isolate have been optimized. This Pseudomonas species was used to produce vinegar from barley malt wine. In this process, the commercial yeast strain, Saccharomyces cerevisiae, was used to produce ethanol from barley malt extract with 7.3 Brix degree. Malt wine with 3.49% ethanol content was obtained in 3 days of fermentation. For acetous fermentation by the bacterial isolate, barley malt wine with 5% ethanol content and 4.7 Brix was used as a substrate. Malt vinegar with a pH of 3.76 and 3.5% titratable acidity was obtained by using the flask method, and malt vinegar with a pH of 3.79 and 3.4% titratable acidity was obtained by using a bioreactor.